Relationship between Waiting Time at the Registration Desk and Patient Satisfaction at Ngebel Ponorogo Health Center - Dea Nisa' Istiqomah (Institut Kesehatan Pelamonia, 2025)
Dea Nisa' Istiqomah, 2025.